Bali Ecological Wisdom and the Transformation of Reporting Accountability: A Critical Point for Balinese Green Agenda - Cokorda Gde Bayu Putra; Ni Ketut Muliati; Putu Cita Ayu; Ni Putu Trisna Windika Pratiwi; Ni Putu Yeni Yuliantari (Universitas Pendidikan Ganesha, 2024)
This article aims to present a transformative approach to reporting by integrating the ecological and spiritual teachings of Sad kerthi from Balinese culture, addressing a significant gap in traditional accounting practices that predominantly focus on financial metrics without incorporating local ecological and spiritual values crucial for business transparency and environmental sustainability. Employing a critical research framework with qualitative content analysis and a reflective approach, the study analyzes how these teachings can be embedded into accounting practices, emphasizing respect for natural symbols and their sanctity. Business entities in Bali are encouraged to actively contribute to preserving the natural environment—mountains, lakes, forests, rice fields, oceans, and the universe—with the goal of developing reporting practices that reflect spiritual, religious, and ecological values.